Musical Elements in the Writing of Felisberto Hernández (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
This study analyses four stories by the great Uruguayan writer Felisberto Hernández in the context of fantastic literature. The stories are El Cocodrilo, El Acomodador, El Balcón and  Mi primer Concierto. In these stories, as in most of his work ―which is fantastic, humorous and absurd― Hernández uses elements originating in his musical training as a professional pianist, musical interpreter and composer. Forms such as improvisation, impromptu, fantasia and divertimento, which rightly belong to musical creation and to composers such as Chopin, Mozart, Schubert and Stravinsky, become significant components of the literary world and the narrative resources of this author.